The fire-eaters - Almond, David (Hodder Children's Books London, 2004)
In 1962 England, despite observing his father's illness and the suffering of the fire-eating Mr. McNulty, as well as enduring abuse at school and the stress of the Cuban Missile Crisis, Bobby Burns and his family and friends still find reasons to rejoice in their lives and to have hope for the future